2015
DOI: 10.1097/md.0000000000000588
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated With False-Negative Endoscopic Biopsy Results After Neoadjuvant Chemoradiotherapy in Patients With Esophageal Squamous Cell Carcinoma

Abstract: The usefulness of endoscopic biopsy following neoadjuvant chemoradiotherapy (nCRT) is limited because of its high false-negative (FN) rates. However, data on the factors associated with FN biopsy results remain scarce. The purpose of this study was to investigate factors associated with FN results on endoscopic biopsies in patients with esophageal squamous cell carcinoma (ESCC) following nCRT.We retrospectively reviewed the records of ESCC patients who were treated at the Chang Gung Memorial Hospital, Taoyuan,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 20 publications
1
8
0
Order By: Relevance
“…The present study confirms that certain endoscopic findings (i. e. endoscopic suspicion of residual tumor) may contribute to a diagnostic strategy for detection of residual esophageal cancer. In addition, and similarly to findings by Chao et al [12], a substantial rate of false-negative biopsies was observed in patients with endoscopic suspicion of residual tumor after nCRT. Outcome should, however, be interpreted with caution because of the small number of patients with this finding in this study.…”
Section: Present Absent Uncertainsupporting
confidence: 84%
See 3 more Smart Citations
“…The present study confirms that certain endoscopic findings (i. e. endoscopic suspicion of residual tumor) may contribute to a diagnostic strategy for detection of residual esophageal cancer. In addition, and similarly to findings by Chao et al [12], a substantial rate of false-negative biopsies was observed in patients with endoscopic suspicion of residual tumor after nCRT. Outcome should, however, be interpreted with caution because of the small number of patients with this finding in this study.…”
Section: Present Absent Uncertainsupporting
confidence: 84%
“…For the purpose of this retrospective study, endoscopy reports were independently reviewed by two blinded investigators (R.D.vdB., B.J.vdW.) based on a predefined case record form with input from upper gastrointestinal endoscopists and previous studies [9,11,12]. The following endoscopic findings were recorded: non-passable stenosis, passable stenosis, suspicion of residual tumor, scar tissue, and ulceration (▶ Fig.…”
Section: Upper Endoscopymentioning
confidence: 99%
See 2 more Smart Citations
“…Owing to recent advances in CRT (resulting in improved pCR rates) and in light of morbidity-related concerns related to esophageal resection after CRT, there is growing debate about whether planned esophagectomy could be avoided in patients without clinically evident disease (clinical CR) after CRT [11][12][13]. The use of optimized panendoscopy examination protocols can improve the diagnostic confidence on the absence of residual cancer at the primary site [14]. However, the lack of residual neoplasms at the primary tumor site does not rule out the presence of regional LN involvement.…”
Section: Commentmentioning
confidence: 99%